DO CARBON EMISSION DISCLOSURES ENHANCE FIRM VALUE? THE MODERATING ROLES OF EARNINGS MANAGEMENT AND GOOD CORPORATE GOVERNANCE - Arlita, Rizki; Musviyanti, Musviyanti; Bone, Hariman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the influence of carbon emission disclosures and firm value by high-profile firms listed on the Indonesian Stock Exchange in 2020-2024. In addition, the study further examined the moderating role of earnings management and good corporate governance on this relationship. The total sample of 19 high-profile firms was obtained using purposive sampling method. The hypothesis testing was conducted using the Moderated Regression Analysis (MRA). The research find that carbon emission disclosures does not have an effect on firm value. Furthermore, earnings management can strengthen the relationship between carbon emission disclosures and firm value. Meanwhile, good corporate governance cannot strengthen the relationship between carbon emission disclosures and firm value. The results contribute to the literature in the fields of carbon emission disclosures and firm value by demonstrating the moderating role of earnings management and good corporate governance, which is not evident in previous studies. It also provides an enhanced perspective on the implications for firms, regulators, policymakers, and stakeholders who are interested in reducing carbon emissions and advancing climate change mitigation goals in line with the net zero emissions (NZE) goal by 2060. The implications of this study highlight the importance for firms to enhance the quality and credibility of carbon emission disclosures to provide stronger positive perception to investors, rather than merely fulfilling regulatory compliances.